Structure, magnetism and magnetocaloric effect in a new triangular lattice compound Gd3Cu9(OH)19Br8. Issue 40 (12th September 2022) - Cheng, Dong-Er; Wang, Yi-Yan; Sun, Yan; Liang, Hui; Wu, Dan-Dan; Li, Qiuju; Sun, Xuefeng; Yue, Xiao-Yu
Abstract : The two-dimensional magnetic lattice of Gd3 Cu9 (OH)19 Br8, where Gd 3+ ions are located in the center of hexagonal holes of the Cu-Kagome lattice. Abstract : A new triangular lattice compound Gd3 Cu9 (OH)19 Br8 has been synthesized by the hydrothermal method. The structure, magnetism and magnetocaloric effect of Gd3 Cu9 (OH)19 Br8 have been studied by X-ray diffraction, magnetic susceptibility, isothermal magnetization and specific heat measurements. In Gd3 Cu9 (OH)19 Br8, the Cu 2+ ions form a Kagome lattice along the ab plane, and Gd 3+ ions are located in the center of hexagonal holes of the Kagome layer. The Cu-sublattice and Gd-sublattice overlap and constitute a magnetic triangular lattice. The temperature dependence of susceptibility and specific heat curves indicate no magnetic transition down to 2 K, suggesting a paramagnetic-like behavior at low temperature. The magnetocaloric effect (MCE) at low temperature has been calculated according to Maxwell's equations. The maximum value of magnetic entropy change −Δ S M is 26.04 J kg −1 K −1 and adiabatic temperature change Δ T ad is 13.79 K, for a field change of 0–7 T, indicating a potential application of this compound in the field of magnetic refrigeration at low temperature. The influence of 4f–3d interaction on magnetism and MCE is also discussed.